HUBUNGAN KADAR PLUMBUM (PB) DALAM DARAH DENGAN PROFIL DARAH PADA WANITA USIA SUBUR DI BREBES TAHUN 2010 - Eko Hartini (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Background. Some of the pesticides used by farmers in Brebes contain Pb heavy metals such as Antracol 70 WP, Dithane M 45 80 WP, Furadan 3G, Goal 240 EC, Buldog 25 EC, Hostathion 200 EC, and Profile 430 EC. The lowest Pb levels is on Goal 240 EC in the amount of 0,87 mg/kg and the highest Pb levels is in Dithane in the amount of 19,37 mg/kg. The fertile women involvement in agriculture activities can cause fertile age women to be exposed by Pb heavy metal contained in pesticides. The absorbed Pb transported by blood to the organs of the body as much as 95%, the Pb in blood bound by erythrocytes and can disturb blood profile.Research Methods. The purpose of this research is to analyze relation between Pb levels in blood with blood profile on fertile age women in agricultural area. This research is an observational research with analytical survey method. The used study design is cross sectional.Research Results. Pb levels in blood of fertile women in Kersana District in Brebes Region still within tolerable limits (average = 25,55 Â± 12,45 Î¼gr/ml) and respondentsâ€™ blood profile on average are still within normal limits except for monocytes levels which is above the standard.Pb levels in blood is related to erythrocytes numbers (p=0,028; RP= 5,02; 95% CI=1,59- 15,86).Keywords : Pb levels in blood, blood profile, the fertile women